KAJIAN KAPASITAS TAMPUNG SALURAN DRAINASE JALAN A.W SYAHRANIE – KOTA SAMARINDA - Ardiansyah, Dedy (KURVA S JURNAL MAHASISWA, 2014)
Drainage is a way of disposal of excess water which is not desirable in a region, as well as ways of overcoming consequences caused by excess water. The purpose and goal is to remove water drainage above ground level beriebihan, lowering and maintaining the water level inundation rather not happen, so a negative result with the inundation and flood water can be avoided.Segment road drainage A.W. Syahranie - Samarinda is the accent that is often flooded, therefore, in the hope the advice or guidance could be for the government to determine local policy in meticulous in infrastructure as well as the city would anticipate a greater possibility of flooding in the AW Syahranie - Samarinda.The method used to perform data collection method and the method log Gumbel type person.From the results of a calculated discharge rancangn 2,5,10 and 25 years gained value - value on every channel, every channel on the field measurement values obtained calculation results of channel dimensions.